2018
DOI: 10.1186/s12894-018-0418-4
|View full text |Cite
|
Sign up to set email alerts
|

Expression and clinical significance of Caveolin-1 in prostate Cancer after transurethral surgery

Abstract: BackgroundProstate cancer is a common malignancy of the male genitourinary system that occurs worldwide. The current research aims to investigate caveolin-1 expression in prostate cancer tissue and its relationship with pathological grade, clinical pathologic staging, and preoperative prostate-specific antigen (PSA) levels.MethodsFrom January 2012 to December 2014, samples from 47 patients with prostate cancer who had received transurethral prostatic resection (TURP) and 20 patients with benign prostatic hyper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…Cav-1 increases the aggressiveness of cancer cells in pancreatic, hepatic, gastric, and prostate cancers. [28][29][30][31][32][33] However, cav-1 deficiency is seen as a driving force in squamous-cell carcinoma and breast cancer. 34,35 It appears that cav-1 exerts diversified effects in different cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Cav-1 increases the aggressiveness of cancer cells in pancreatic, hepatic, gastric, and prostate cancers. [28][29][30][31][32][33] However, cav-1 deficiency is seen as a driving force in squamous-cell carcinoma and breast cancer. 34,35 It appears that cav-1 exerts diversified effects in different cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies indicated that caveolin-1 was related to endocytosis, signaling and lipid disorders, while recent studies focused on clarifying its relevance in cancer. Caveolin-1 is expressed in esophageal carcinoma ( 19 , 20 ), prostate cancer ( 8 17 ), colon cancer ( 21 ), breast cancer ( 22 ), bladder cancer ( 23 ), lung cancer ( 24 ), and other cancers ( 25 , 26 ), and acts as a tumor promoter or suppressor. As a tumor promoter, high expression of caveolin-1 drives tumorigenesis by inhibiting apoptosis, facilitating anchorage-independent growth, drug resistance as well as metastasis ( 27 , 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the inclusion and exclusion criteria, 10 studies (8)(9)(10)(11)(12)(13)(14)(15)(16)(17) were enrolled, which included 3976 cases of prostate cancer, of which 962 were positive for caveolin-1. Moreover, 72 cases were high-grade intraepithelial neoplasia of prostate (HGPIN), of which 15 were positive for caveolin-1.…”
Section: Characteristics Of Enrolled Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…CAV1 is one of the critical components of the integral membrane protein that makes up caveolins. It has been reported to be associated with esophageal carcinoma, [ 15 , 16 ] prostate cancer, [ 17 , 18 ] colon cancer, [ 19 ] breast cancer, [ 20 ] bladder cancer, [ 21 ] lung cancer, [ 22 ] and others, [ 23 , 24 ] which can promote or suppress tumor occurrence and development.…”
Section: Discussionmentioning
confidence: 99%